On some energy aspects of the monsoon depressions during its life cycle - RAJAMANI, S.; KULKARNI, J. R. (MAUSAM, 1986)
Relative vorticity, energy terms, energy conversion terms and the transports of momentum and heat were computed for the period from 1. to 1.0 July 1.973, which covered the life cycle of a monsoon depression in older to study the energy exchange between the different components of the monsoon circulation and the transports of momentum and heat during strengthening and decaying period of the depression. Interestingly, there were two depressions, one over the Bay of Bengal and the other over the Arabian Sea co-existing during this period. From this computational study it is inferred that whereas the system over the Bay of Bengal apparently formed simultaneously at all levels in the lower troposphere, the second system formed first at a higher level around 700 mb and then descended to the surface. Both zonal and eddy kinetic energy as well as the zonal available potential energy increased with the strengthening of the systems but there is no systematic change in the eddy available potential energy. Also, during this period the northward transport of the momentum in the entire troposphere and the southward transport of heat in the lower troposphere increased. In general, the eddies gained available potential energy from the zonal current whereas the zonal current gained kinetic energy in the lower levels and lost it in the higher levels.